Strategies to reduce rework in software development on an organisation in Mauritius - Ramdoo, Vimla; Huzooree, G. (Academy & Industry Research Collaboration Center (AIRCC), 2015)
Rework is a known vicious circle in software development since it plays a central role in the generation of delays, extra costs and diverse risks introduced after software delivery. It eventually triggers a negative impact on the quality of the software developed. In order to cater the rework issue, this paper goes in depth with the notion of rework in software development as it occurs in practice by analysing a development process on an organisation in Mauritius where rework is a major issue. Meticulous strategies to reduce rework are then analysed and discussed. The paper u ultimately leads to the recommendation of the best strategy that is software configuration management to reduce the rework problem in software development.